2017
DOI: 10.1097/pcc.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulmonary Function and Quality of Life in Children After Acute Respiratory Distress Syndrome: A Feasibility Investigation

Abstract: Objective Determine the feasibility of pulmonary function (PFT) and quality of life (QOL) evaluations in children after Acute Respiratory Distress Syndrome (ARDS). Design A prospective follow-up feasibility study Setting A tertiary pediatric intensive care unit Patients Children <18 year old with ARDS admitted between 2000 and 2005. Measurements and Main Results PFTs and QOL questionnaires performed approximately 12-months post-illness were analyzed and correlated to in-hospital clinical parameters. QO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
1
42
2
Order By: Relevance
“…With a focus on specific diseases and conditions, the SPROUT study, a recent international point prevalence study of pediatric sepsis, showed that 17% of sepsis survivors suffered moderate to severe disability . Among children who survived ARDS, Ward et al . suggested that up to one‐third showed pulmonary dysfunction and that their quality‐of‐life scores 12 months after discharge were lower than those in asthmatic children.…”
Section: Introductionmentioning
confidence: 99%
“…With a focus on specific diseases and conditions, the SPROUT study, a recent international point prevalence study of pediatric sepsis, showed that 17% of sepsis survivors suffered moderate to severe disability . Among children who survived ARDS, Ward et al . suggested that up to one‐third showed pulmonary dysfunction and that their quality‐of‐life scores 12 months after discharge were lower than those in asthmatic children.…”
Section: Introductionmentioning
confidence: 99%
“…A recent longitudinal study of 29 PARDS survivors highlighted that 80% experienced pulmonary function abnormalities at 3 months after ICU discharge . Another documented mild‐to‐moderate obstructive pulmonary function deficits or diffusion abnormalities in one‐third of the 17 survivors who performed pulmonary function testing 12 months after an ARDS episode . However, both studies used adult ARDS diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another documented mild-to-moderate obstructive pulmonary function deficits or diffusion abnormalities in one-third of the 17 survivors who performed pulmonary function testing 12 months after an ARDS episode. 11 However, both studies used adult ARDS diagnostic criteria. Compared to the adult Berlin 3 and American European Consensus Conference 12 definitions, the PALICC definition identifies nearly twice as many children with ARDS, including many with milder disease but also a subset of patients with severe ARDS that were not identified by adult definitions.…”
Section: Introductionmentioning
confidence: 99%
“…A multimodal approach to prevent, detect, and treat delirium should be implemented (47). Long-term effects on renal, hepatic, and lung function should be monitored as survivors frequently have prolonged impairment (48). Lastly, many survivors have prolonged functional impairment that may benefit from rehabilitation services (49).…”
Section: What Is the Best Way To De-escalate Therapy And Promote Recomentioning
confidence: 99%